Regionalizáció, területi reformok és közigazgatási térfelosztás Közép-Európában 1. : csehszlovák és szlovák tanulságok - Gulyás, László (Közép-Európai Közlemények, 2009)
According to literature dealing with the reforms of public administration, the territorial division of a country is purely a professional issue. The political elite should elaborate the division on the basis of the geographical, economic and other important characteristics of the given country in a way that is in harmony with its governing system. But in the countries of Central-Europe this theoretical model is often modified because of the presence of national minorities. The paper analyzes the reforms of public administration of different Czecho-slovak and Slovak states. The final conclusion is the following: from 1918 to nowadays the different states were all for homogenization, and were utilizing both regionalization and regionality for their own purposes.